Control of marine leeches infecting hybrid grouper Epinephelus fuscoguttatus >< E. lanceolatus with garlic Allium sativum powder - Aminatul Zahra; Dwi Septiani Putri (Indonesian Society of Scientific Aquaculture (ISSA), 2023)
Grouper has a large market demand and to meet this, the intensification of grouper cultivation is being carried out more massively. This situation increases the spread of diseases, one of which is sea leeches. This study aimed to obtain the concentration and duration of immersion garlic powder for the control of leeches that infects hybrid grouper (Epinephelus fuscoguttatus >< E. lanceolatus). This study used a factorial randomized design (concentration factor and garlic soaking time factor) with nine treatments and three replications. The treatment in this study was a combination of 0 g/L 0,375 g/L, and 0,750 g/L garlic powder concentration and immersion times of 20 minutes, 40 minutes, and 60 minutes. The results showed that concentrations of 0.375 g/L and 0.750 g/L were able to significantly reduce the intensity of leeches infecting hybrid grouper, namely 7.43% and 13.29%, respectively. The interaction between concentration and duration of immersion garlic powder on the percentage decrease in intensity was not significantly different. Immersion of garlic powder for 60 minutes was able to reduce the intensity of the leech by 9.56% and the results were significantly different with the immersion time of 20 and 40 minutes. However, the concentration and duration of soaking garlic powder were not able to reduce the prevalence of hybrid grouper infected with leeches. The R2 value of 0.748 means that there is a relationship between garlic powder concentration and the decrease in leech intensity in hybrid grouper. Powder garlic concentration of 0.750 g/L and immersion time of 60 minutes was able to reduce the intensity of leeches in hybrid grouper, but it was not effective in reducing the prevalence of fish infected with leeches. Keyword: garlic, hybrid grouper, sea leech ABSTRAK Ikan kerapu memiliki permintaan pasar yang besar dan untuk memenuhi hal tersebut, maka intensifikasi budidaya ikan kerapu perlu dilakukan secara lebih masif. Keadaan ini meningkatkan penyebaran penyakit, salah satunya lintah laut. Penelitian ini bertujuan untuk menentukan konsentrasi dan lama perendaman tepung bawang putih untuk pengendalian lintah yang menginfeksi ikan kerapu hibrida (Epinephelus fuscoguttatus >< E. lanceolatus). Penelitian ini menggunakan rancangan acak faktorial (faktor konsentrasi dan faktor lama perendaman bawang putih) dengan sembilan perlakuan dan tiga ulangan. Perlakuan di dalam penelitian ini adalah kombinasi antara konsentrasi tepung bawang putih 0%, 3%, 6%, dan lama perendaman 20 menit, 40 menit, dan 60 menit. Hasil penelitian menunjukkan bahwa konsentrasi 0,375 mg/L dan 0,750 mg/L mampu menurunkan intensitas lintah yang menginfeksi ikan kerapu cantang secara signifikan, yaitu sebesar 7,43% dan 13,29%. Interaksi antara konsentrasi dan lama perendaman bubuk bawang putih tidak berbeda signifikan terhadap penurunan intensitas lintah. Perendaman bawang putih selama 60 menit mampu menurunkan intensitas lintah sebesar 9,56% dan hasilnya berbeda signifikan dengan lama perendaman 20 dan 40 menit. Namun konsentrasi dan lama perendaman bawang putih tidak mampu menurunkan angka prevalensi kerapu cantang yang terinfeksi lintah. Nilai R2 sebesar 0,748 menunjukkan hubungan antara konsentrasi bubuk bawang putih dan penurunan intensitas lintah pada ikan kerapu cantang. Konsentrasi bawang putih 0,750 g/L dan waktu perendaman 60 menit mampu menurunkan intensitas serangan lintah pada kerapu hibrida, namun tidak efektif menurunkan prevalensi ikan terinfeksi lintah. Kata kunci: bawang putih, ikan kerapu cantang, lintah laut